Educational Media Design for Heart Attack First Aid Based on Motion Graphic at Harbour Energy - Agung Pradana; Sherly Agustini (Rey Media Grafika, 2024)
Heart attacks are a leading cause of death worldwide, requiring quick and accurate first aid. However, workplace education on first aid for heart attacks remains limited. This study aims to design an educational medium using motion graphics to enhance employees’ understanding at Supply Base Harbour Energy Batam of first aid procedures for heart attacks. This research adopts the Multimedia Development Life Cycle (MDLC) model, which consists of six stages: concept, design, material collecting, assembly, testing, and distribution. Theories on multimedia and visual-based education support this study. The input data were obtained from observations and interviews with company supervisors as primary data, while secondary data were collected from relevant literature. A qualitative research approach with descriptive analysis was employed, and the sample consisted of employees at Supply Base Harbour Energy Batam. The results, tested using the black box testing method, indicate that the developed motion graphic effectively conveys information clearly and engagingly, assisting employees in recalling and understanding first aid procedures. This research provides an innovative solution to enhance awareness and preparedness in handling emergencies, thereby reducing the risk of fatal outcomes from heart attacks in the workplace.